On reduced stable pair invariants - Oberdieck, Georg (Mathematische Zeitschrift, 2018)
Let X = S x E be the product of a K3 surface S and an elliptic curve E. Reduced stable pair invariants of X can be defined via (1) cutting down the reduced virtual class with incidence conditions or (2) the Behrend function weighted Euler characteristic of the quotient of the moduli space by the translation action of E. We show that (2) arises naturally as the degree of a virtual class, and that the invariants (1) and (2) agree. This has applications to deformation invariance, rationality and a DT/PT correspondence for reduced invariants of S x E.
Online veröffentlicht: 20. Oktober 2017
Gesehen am 14.01.2025